2018
DOI: 10.1016/j.bcp.2018.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical pharmacology of psychoactive substituted N-benzylphenethylamines: High potency agonists at 5-HT2A receptors

Abstract: The use of new psychoactive substituted 2,5-dimethoxy-N-benzylphenethylamines is associated with abuse and toxicity in the United States and elsewhere and their pharmacology is not well known. This study compares the mechanisms of action of 2(2,5-dimethoxy-4-methylphenyl)-N-(2-methoxybenzyl)ethanamine (25D-NBOMe), 2-(4-ethyl-2,5-dimethoxyphenyl)-N-(2-methoxybenzyl)ethanamine (25E-NBOMe), 2-(2,5dimethoxyphenyl)-N-(2-methoxybenzyl)ethanamine (25H-NBOMe), 2-(((4-iodo-2,5dimethoxyphenethyl)amino)methyl)phenol (25I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 36 publications
(60 reference statements)
3
62
0
Order By: Relevance
“…Psychedelic phenethylamine derivatives are mostly but not exclusively chemically modified at the phenyl ring. The introduction of an N-benzylmethoxy (''NBOMe'') group has been shown to increase the potency of the resulting derivatives (Eshleman et al 2018;Halberstadt 2017;Heim 2004;Rickli et al 2015c). The incorporation of 2 0 -and 5 0 -methoxy groups into rigid rings resulted in tetrahydrobenzodifuran and benzodifuran analogs that have been sold as designer drugs.…”
Section: Phenethylaminesmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychedelic phenethylamine derivatives are mostly but not exclusively chemically modified at the phenyl ring. The introduction of an N-benzylmethoxy (''NBOMe'') group has been shown to increase the potency of the resulting derivatives (Eshleman et al 2018;Halberstadt 2017;Heim 2004;Rickli et al 2015c). The incorporation of 2 0 -and 5 0 -methoxy groups into rigid rings resulted in tetrahydrobenzodifuran and benzodifuran analogs that have been sold as designer drugs.…”
Section: Phenethylaminesmentioning
confidence: 99%
“…Similar to other psychedelics, substituted phenethylamines mainly interact with serotonergic receptors, with the highest affinity for 5-HT 2A receptors (Eshleman et al 2018;Kolaczynska et al 2019;Luethi et al 2018d;Rickli Fig. 8 Correlation between reported clinical potencies and in vitro human 5-HT 2A receptor affinities of a variety of psychedelics.…”
Section: Mechanism Of Action Of Phenethylaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies indicated that NBOMe compounds are ultrapotent and highly efficacious agonists of 5-HT 2A and 5-HT 2C receptors (Ki values in low nanomolar range), with more than 1000-fold selectivity for 5-HT 2A compared with 5-HT 1A . The compounds display higher affinity for 5-HT 2A receptors than their 2C counterparts and have markedly lower affinity, potency, and efficacy at the 5-HT 2B receptor than at 5-HT 2A or 5-HT 2C (Juncosa et al, 2013;Nichols et al, 2015;Rickli et al, 2015;Elmore et al, 2018;Eshleman et al, 2018). In addition, NBOMes have a significant affinity (Ki < 300 nM) for adrenergic α 1 receptors but not so H 1 -histamine, dopamine D 1 , D 2 , and D 3 receptors or the monoamine transporters DAT, NET, or SERT (Nichols et al, 2015;Elmore et al, 2018;Eshleman et al, 2018).…”
Section: Pharmacology Of Nbomesmentioning
confidence: 99%
“…Phenethylamines are agonists of the serotonin (5-HT, 5-hydroxytryptamine) receptors [4]. The N-benzyl substitution in phenethylamines (usually from the 2C-X family, such as 2C-I and 2C-B) improve the binding and functional activity in 5-HT receptors, with N-(2-hydroxybenzyl) substituted substances usually presenting the highest affinities to the 5-HT 2A receptor [4][5][6].…”
Section: Introductionmentioning
confidence: 99%